2017
DOI: 10.7249/rr1811
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Designed Care Models and Culture of Health: Review of Three Case Studies

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Future of Nursing 2020–2030 report identifies “addressing the social needs and SDOH in the community” as one of the four opportunities nurses have to impact overall health equity (The National Academies of Sciences, Engineering, and Medicine, 2021). Nurse led programs have provided promising models to improve population health outcomes through interventions that address social determinants simultaneously with traditional biomedical needs (Martsolf et al., 2017). Given the complexity and multifaceted interactions of social determinants on health outcomes, selecting impactful screening tools, interventions, linkages, and referrals at the point of public health practice may be daunting to operationalize and scale within resource constrained practice environments.…”
Section: Discussionmentioning
confidence: 99%
“…The Future of Nursing 2020–2030 report identifies “addressing the social needs and SDOH in the community” as one of the four opportunities nurses have to impact overall health equity (The National Academies of Sciences, Engineering, and Medicine, 2021). Nurse led programs have provided promising models to improve population health outcomes through interventions that address social determinants simultaneously with traditional biomedical needs (Martsolf et al., 2017). Given the complexity and multifaceted interactions of social determinants on health outcomes, selecting impactful screening tools, interventions, linkages, and referrals at the point of public health practice may be daunting to operationalize and scale within resource constrained practice environments.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, PHNs are incorporating skills from several domains of the PHN core competencies, including domains 1 through 5 (CPHNO, 2021). As a specialty within one of the most trusted professions, PHNs serve as important team members in addressing unmet health needs within a community and working to build a Culture of Health (Hassmiller & Kuehnert, 2019; Martsolf et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The need to address policy changes and socio‐economic factors is similarly confirmed in a comprehensive study of the American Academy of Nursing Edge Runner Models (Martsolf, Mason, Sloan, Sullivan, & Villarruel, ; Martsolf et al., ;), which are innovative nurse‐designed care models with evidence of improved clinical and financial outcomes. Many of these models are research based and have demonstrated regional and also national impact and address a multitude of health (pregnancy to elder care) and health system (coordination of care, delivering comprehensive primary care) issues.…”
Section: Innovation and Sustainability In Researchmentioning
confidence: 92%